2019
DOI: 10.1093/database/baz062
|View full text |Cite
|
Sign up to set email alerts
|

Endometriosis Knowledgebase: a gene-based resource on endometriosis

Abstract: Endometriosis is a complex, benign, estrogen-dependent gynecological disorder with an incidence of ~10% women in reproductive age. The implantation and growth of endometrial cells outside the uterus leads to the development of endometriosis. Endometriosis is also associated with comorbid conditions like cardiovascular and autoimmune diseases. The absence of non-invasive diagnostic markers, delayed diagnosis, high risk of recurrence of the disease on surgical removal of the tissue and absence of a definitive cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 78 publications
1
18
0
3
Order By: Relevance
“…In the groups of 35-45 years and over 45 years of age, respectively, the data were as follows: ovaries (74% and 57.14%), peritoneum (37.33% and 14.29%) and fallopian tubes (31.33% and 14.29%). The most persistent complaint reported by the respondents in all age groups was pain during menstruation (group 18-25 years old: 80.43%, group 25 ). Most respondents expressed their willingness to obtain assistance in the search for the optimal method of treatment (66.67%) and therapy financing (63.89%).…”
Section: Group Characteristicsmentioning
confidence: 98%
See 1 more Smart Citation
“…In the groups of 35-45 years and over 45 years of age, respectively, the data were as follows: ovaries (74% and 57.14%), peritoneum (37.33% and 14.29%) and fallopian tubes (31.33% and 14.29%). The most persistent complaint reported by the respondents in all age groups was pain during menstruation (group 18-25 years old: 80.43%, group 25 ). Most respondents expressed their willingness to obtain assistance in the search for the optimal method of treatment (66.67%) and therapy financing (63.89%).…”
Section: Group Characteristicsmentioning
confidence: 98%
“…The adverse effects experienced by patients with endometriosis significantly contribute to problems with productivity, relationship difficulties, and social dissatisfaction. Endometriosis is therefore a pathology that can significantly affect the quality of women's life in multiple dimensions [1,24,25]. Modern treatment of endometriosis should be personalised using a patient-centred, interdisciplinary approach.…”
Section: Introductionmentioning
confidence: 99%
“…The gene network of endometriosis includes genes of hormones and their receptors, tumor suppressors, the detoxification systems, cytokines, and their receptors, embryonic development and cell proliferation, and others, involved in more than 30 metabolic ways ( Fig. 1) [91]. Epigenetic factors (e.g., level of DNA methylation, modification of histone proteins, microRNA) are important in the development of endometriosis [92].…”
Section: Genes Involved In Endometriosis Developmentmentioning
confidence: 99%
“…It has been indicated that autoimmune disorders could occur more often among those with endometriosis. However, endometriosis’s actual mechanism and genetic etiology are unknown ( 9 ).…”
Section: Introductionmentioning
confidence: 99%